Factors influencing knowledge transfer and the mediating effect of shared vision involving expatriates and host country nationals in the Klang Valley, Malaysia - Zulkifly, Nurul Afiqah (2017)
Many past studies on knowledge transfer which focused on factors such as the behaviour of knowledge senders and organizational practice; however, they are limited in terms of considering individual factors such as cultural intelligence (CQ) and feedback-seeking behaviour (FSB) as well as shared vision as a mediator. In addition, there was a strong need for a study on bi-directional knowledge transfer involving both expatriates and host country nationals (HCNs) as most of the studies were conducted uni-directionally.